The management of postherpetic neuralgia. - Bowsher, D. (BMJ Group, 1997)
Postherpetic neuralgia is defined as pain persisting, or recurring, at the site of shingles at least three months after the onset of the acute rash. Thus defined, at least half of shingles sufferers over the age of 65 years develop postherpetic neuralgia. In addition to increasing age, less important risk factors for postherpetic neuralgia are pain severity of acute shingles and trigeminal distribution. Postherpetic neuralgia accounts for 11-15% of all referrals to pain clinics and would, in fact, be far more effectively dealt with in primary care. Effective treatment of acute shingles by systemic antivirals at the appropriate time may have some effect in reducing the incidence of postherpetic neuralgia, making it easier to treat with tricyclics and greatly reducing scarring (25% of all cases affect the face). Pre-emptive treatment with low-dose tricyclics (ami- or nor-triptyline 10-25 mg nocte) from the time of diagnosis of acute shingles reduces the incidence of postherpetic neuralgia by about 50%. Established postherpetic neuralgia should be vigorously treated with adrenergically active tricyclics in a dose rising over two or three weeks from 10-25 mg to 50-75 mg. Positive relaxation should also be used. Carbamazepine, like conventional analgesics, is of little or no value. Failure of tricyclics to effect relief within eight weeks calls for specialist treatment. North American practitioners in particular believe that some opioids (e.g., oxycodone) may be helpful in otherwise intractable cases.